Orthodox Christians and Islam in the Postmodern Age - Sharp, Andrew (Leiden : BRILL, 2012)
This book is the first comprehensive attempt to assess an Orthodox Christian 'position' on Islam. It demonstrates how a growing number of ordained and lay leaders have reframed the discussion within the Orthodox Church, while participating in dialogue with Muslims.
2007 and Beyond: Renewed Commitment to Dialogue and the Synaxis of the Primates of the Orthodox ChurchesConclusions; Conclusion; List of References; Index
Description based upon print version of record.
Keywords: Islam -- Relations -- Orthodox Eastern Church; Orthodox Eastern Church -- Relations -- Islam; Orthodox Eastern Church; Religion; Islam -- Relations -- Orthodox Eastern Church; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books